Stingless bee nest for housing area in Malaysia - Abdul Rahman, Julaila; Amer, Nur Kamaliah; Atef, Nagwaen; Halim, Mohd Azam (Kulliyyah of Architecture and Environmental Design, 2019)
Meliponiculture is an activity of stingless beekeeping, where the colony of stingless bees extracted from the wild for the purpose of profit. It is the art and science of keeping stingless bees for honey, pollen, resin and ecological services. With the managing of bees in artificial hives, it enables beekeeper to propagate colonies and produce products such as honey, pollen and propolis. This study aims to propose a suitable design for stingless bee nest, which will be using in a small housing area in Malaysia. Colonies of G. Thoracica were used to study the nest structure and growth, foraging activity and morphometry of worker bee. With this study, it is hoped that many more users can involve in meliponiculture for domestic purposes, which will also contribute to the Malaysian economy in general.